Prevalence and clinical presentation of headache in a National Neurofibromatosis 1 Service and impact on quality of life. (5th June 2015) - Afridi, Shazia K.; Leschziner, Guy D.; Ferner, Rosalie E.
<x xml:space="preserve">Abstract</x> In our clinical practice, we noticed a high frequency of headaches amongst NF1 patients. We sought to characterize the phenotype and prevalence of headache in our cohort of NF1 patients attending the London NF clinic and to determine the impact on quality of life. Participants over the age of 16 fulfilling diagnostic criteria for NF1 from the general NF1 outpatient clinics at Guy's and St. Thomas' NHS Foundation Trust and the nationally commissioned Complex NF1 service were asked to fill in a questionnaire during the clinic consultation. Data were recorded regarding the headache frequency, intensity, duration, and phenotype, and a validated quality of life questionnaire, HIT‐6 was also completed by the participant. IHS (International Headache Society) criteria were used to diagnose migraine. One hundred fifteen patients (48 males, 67 females) completed the questionnaire. The age range of participants was 16–67 with a mean age of 36 years. Twenty‐five reported no headaches. Seventy‐five (65%) fulfilled IHS diagnostic criteria for migraine (15 with aura). The mean HIT‐6 score was 56 (out of a maximum 78) implying a significant effect on quality of life. Migraine is common in our NF1 population and has a significant impact on quality of life. Patients may not volunteer information regarding headache and this should be actively sought during consultations and the headache phenotype should be carefully characterized. © 2015 Wiley Periodicals, Inc.